2009
DOI: 10.1590/s1516-35982009000700001
|View full text |Cite
|
Sign up to set email alerts
|

Cloreto de sódio, benzocaína e óleo de cravo-da-índia na água de transporte de tilápia-do-nilo

Abstract: RESUMO -Testou-se a ação de diferentes concentrações de cloreto de sódio, benzocaína e óleo de cravo-da-índia na sobrevivência de alevinos e juvenis de tilápia (Oreochromis niloticus), linhagem chitralada, por 5 horas visando ao transporte.Utilizaram-se 1.350 alevinos (9,74 ± 0,04 g e 6,79 ± 0,01 cm) e 270 juvenis (29,6 ± 0,06 g e 11,52 ± 0,01). Os peixes foram mantidos em jejum por 24 horas em quatro caixas de amianto (500 L) com aeração constante. Em seguida, os peixes foram distribuídos em 54 sacos plástico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
1
14

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 12 publications
1
13
1
14
Order By: Relevance
“…When it is present in large quantities in the environment, ammonia can elicit adverse effects in fish, including degeneration of the skin, damage to the gills and kidneys and even retardation of fish growth (Soderberg, 1994). Because anesthetics decrease the metabolic activity of fish, it is believed that their addition to the water can reduce the rate of ammonia excretion, thereby improving the water quality (Oliveira et al, 2009). However, in this study, no significant differences in ammonia concentration were found between the different treatments at each salinity level.…”
Section: Experiments 2 -Transportcontrasting
confidence: 70%
“…When it is present in large quantities in the environment, ammonia can elicit adverse effects in fish, including degeneration of the skin, damage to the gills and kidneys and even retardation of fish growth (Soderberg, 1994). Because anesthetics decrease the metabolic activity of fish, it is believed that their addition to the water can reduce the rate of ammonia excretion, thereby improving the water quality (Oliveira et al, 2009). However, in this study, no significant differences in ammonia concentration were found between the different treatments at each salinity level.…”
Section: Experiments 2 -Transportcontrasting
confidence: 70%
“…Os peixes anestesiados com Aqui-S, cujo principio ativo é o isoeugenol, não necessitam de depuração (Ross & Ross, 2008). Os resultados obtidos neste e em outros estudos com espécies criadas no Brasil, como o matrinxã, lambari e a própria tilápia (Inoue et al, 2003;Oliveira et al, 2009;Pereira-da-Silva et al, 2009) indicam que o óleo de cravo e seus derivados são candidatos à liberação para uso em peixes; entretanto, deve haver rigor em relação ao tempo de abate após exposição ao anestésico.…”
Section: Methodsunclassified
“…Similarly, clove oil (5 mg L -1 ) can mitigate the stress response in the matrinxã, Brycon amazonicus, subjected to transport, as it prevents increases of plasma glucose, cortisol, lactate, ammonia, Cl -and K + (Inoue et al, 2005). Furthermore, benzocaine (0 or 20 mg L -1 ) and clove oil (0, 2, or 5 mg L -1 ) can be used as anesthetics for transport based on the observation that the survival of the Nile tilapia, Oreochromis niloticus, was satisfactory (general average of 97.26%) after 5 h of transport (Oliveira, 2009). Largemouth bass, Micropterus salmoides, transported using 5 -9 mg L -1 of clove oil presented a loss of reactivity and reduced cardiac output while maintaining equilibrium and recovering more rapidly than non-anesthetized controls (Cooke et al, 2004).…”
Section: Transportmentioning
confidence: 99%